Realizing Disaster-Resilient Tourism: The Role of BPBD in Supporting Destination Sustainability in Badung Regency - I Ketut Murdika (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Abstract Badung Regency, as a major tourism hub in Bali, faces significant risks of natural disasters, including earthquakes, tsunamis, tidal flooding (coastal flooding), and forest fires. The region's economic dependence on the tourism sector underscores the importance of a robust disaster management system. This study aims to analyze the strategic role of the Regional Disaster Management Agency (BPBD) in building resilient tourism destinations in Badung Regency. Using a descriptive qualitative approach with case studies, data were collected through in-depth interviews, field observations, and documentation studies. The results indicate that the Badung BPBD has initiated evacuation training, disaster hazard maps, and simulations in tourism areas. However, resource limitations, challenges in cross-sector coordination, and the lack of integration of disaster preparedness into destination management remain key challenges. Recommendations include the development of technical regulations for tourism-related Disaster Risk Reduction (DRR), strengthening institutional capacity, and establishing a cross-sector coordination forum. Keywords: BPBD, Disaster-Resilient Tourism, Badung Regency, Destination Sustainability, Disaster Risk Reduction